The role of gender and group preferences in problem-finding and problem-solving - Motlaq Abuhadeeda; Amthal Alaifan; Eid G. Abo Hamza (Institute of Advanced Engineering and Science, 2026)
Creative problem-solving is a critical skill for 21st-century learners, yet its relationship with gender and creativity preferences among gifted students remains underexplored. This study investigated how gender and individual versus group creativity preferences influence problem-finding and problem-solving abilities in intellectually gifted secondary students in Kuwait. A sample of 98 participants was assessed using the realistic problem generation and presented problems evaluations and the collectivism/individualism creativity preference scale. Statistical analysis included cluster analysis and the Point-Biserial correlation coefficient (Pbis). Results revealed that individual creativity had a stronger correlation with problem-solving skills than group creativity, while gender showed no significant effect. These findings support the development of personalized, gender-neutral educational strategies that nurture the distinct creative strengths of gifted learners to optimize academic performance.